Ginsenoside Rg1 Alleviates Lipopolysaccharide-Induced Fibrosis of Endometrial Epithelial Cells in Dairy Cows by Inhibiting Reactive Oxygen Species-Activated NLRP3 - Liangli Song; Linnan Wang; Xiangchen Li; Longfei Xiao (Animals, 2023)
Abnormal function and the fibrosis of endometrium caused by endometritis in cows may lead to difficult embryo implantation and uterine cavity adhesions. Emerging evidence indicates that ginsenoside Rg1 can effectively resist inflammation and pathological fibrosis in different organs. It is hypothesized that ginsenoside Rg1 may possess the potential to mitigate endometrial fibrosis induced by lipopolysaccharides (LPS) in dairy cows. Herein, a model of LPS-stimulated fibrosis was constructed using bovine endometrial epithelial cell line (BEND) cells and ICR mice. Western blotting was used to detect the protein level, and reactive oxygen species (ROS) content was measured by means of DCFH-DA. The uterine tissue structure was stained with H&E and Masson staining. The murine endometrium was assessed for oxidative stress by detecting the concentration of MDA together with the activity of enzymatic antioxidants SOD and CAT. Ginsenoside Rg1 interfered with NLRP3 activation by reducing ROS generation. After the application of ROS inhibitor NAC and NLRP3 inhibitor MCC950, ginsenoside Rg1 could interfere in the ROS/NLRP3 inflammasome signaling pathway by suppressing the epithelial–mesenchymal transition (EMT) of BEND cells. Our in vivo data showed that ginsenoside Rg1 relieved endometrial fibrosis of the mouse model of LPS-induced endometritis by restraining the ROS/NLRP3 inflammasome signaling pathway. Ginsenoside Rg1 inhibits LPS-induced EMT progression in BEND cells probably by inhibiting the activation of ROS-NLRP3 inflammasome.